Exploring Internal Assessment System Management: Voices from Master's Level Students of Tribhuvan University (Solukhumbu Multiple Campus Research Journal, 2025)
Assessment is an essential element of university education as it shapes students' learning outcomes and processes. One powerful strategy for incrementally improving student performance involves continuous assessment. Internal assessment management make sure nondiscriminatory evaluation, promotes continuous learning, enhances competence, and influences students’ academic performance for overall educational outcomes. This study aimed to examine students' observations on internal assessment in relation to their academic performance and motivation. The study applied a qualitative research design. We collected informations from the students and transcribed into Devanagari script, than translated it into English, coded the quotation, and developed the themes inductively. Findings of this study included some uncomfortable circumstances regarding academic writing, presentation skills, assessment preparation, and regular attendance. In spite of this, students are excited to utilise new information and are curious about what they are learning as they strive to complete the internal assessment tasks. Therefore, for internal assessment to be implemented and used effectively, the course structure and student characteristics should be taken into consider. Communicating with students about the goals and advantages of continuous assessment may be the key to minimise the possible adverse consequences of continuous, graded assessments, in addition to increasing their participation in regular, non graded testing. The semester system has been demonstrated to work; students have to study within it, and it has been improved so much that it is completely unrecognisable. Students who want to learn more about the system must apply from an earlier stage. In the end, regular classroom activities and communication chain interconnections help students become better at using this system.